A conceptual framework on issues and challenges of international migrant labors in Malaysia - Mohd Shariff, Nurhazani; Abd Ghani, Nur Syafiqah (INSInet Publications, 2016)
Background: International migrant labors currently play a vital role in the planning process of human resource for a country.Malaysia is also recruiting the international migrant labors to fulfill several problems such as labor shortages, high operation costs and training costs.Objective: This paper discusses several issues and challenges of international migrant labors with the purpose of developing a conceptual framework for further research.Results: The discussion from previous literature highlighted three major aspects which should be considered in the planning process of recruiting international migrant labors namely, push factors (both involving the country and labors), pull factors and negative impact factors.Conclusion: The conceptual framework on issues and challenges of international migrant labors may provide valuable guide to the stakeholders of the country in planning for future recruitment by taking into account the negative impacts particularly concerning the local people.